Zooming into the L2 Speech Fluency Markers of Anxious and Non-Anxious Advanced L2 Learners – an Extreme Case Sampling Report - Szyszka, Magdalena; Lintunen, Pekka (Research in Language, 2023)
The study examines selected temporal markers of L2 utterance fluency in the speech of advanced L2 learners who exhibit high (HLA) and low (LLA) language anxiety levels. Out of the pool of 59 participants, six HLA and six LLA individuals were selected for an in-depth analysis on the basis of their scores on the Foreign Language Classroom Anxiety Scale (the FLCAS) (Horwitz, Horwitz, & Cope, 1986). Speech samples from a monologue task were examined for selected L2 utterance fluency measures: filled (FP) and silent pause (SP) frequency, mean length of silent pause (MLSP), articulation rate (AR), speech rate (SR), and mean length of run (MLR). The results provided insights into the L2 speech fluency profiles of anxious and non-anxious individuals. The analysis disclosed relatively higher frequency and disparate application of FPs, slower speed of speech, and more varied profiles in MLR in the HLA group as compared to the LLA group. The findings yield pedagogical and methodological implications.